2019
DOI: 10.1002/app.47680
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and electrical properties of polypyrrole–bimetallic oxide composites

Abstract: In this study, polypyrrole (PPy) and its bimetallic oxide composites (PPy-V 2 O 5 -MnO 2 ) were synthesized via a modified chemical oxidation polymerization method in the aqueous medium with FeCl 3 Á6H 2 O as an oxidant. The synthesized materials were characterized with various analytical techniques to investigate their structural, crystallographic, thermal, morphological, optical, and electrical properties. The Fourier transform infrared study confirmed the successful synthesis of the materials, whereas the X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In the pure form of PPy, the authors observed the pores and the weak linkage (in polymeric chains) in their structural morphology. Due to this, no proper path was framed for the movement of the charge carrier, which reduced the conductivity of PPy [ 96 ]. The parameters important for the electrical conductivity of PPy are reaction temperature, ratio of oxidant to pyrrole, reaction time, and processing method.…”
Section: Properties Of Polypyrrolementioning
confidence: 99%
“…In the pure form of PPy, the authors observed the pores and the weak linkage (in polymeric chains) in their structural morphology. Due to this, no proper path was framed for the movement of the charge carrier, which reduced the conductivity of PPy [ 96 ]. The parameters important for the electrical conductivity of PPy are reaction temperature, ratio of oxidant to pyrrole, reaction time, and processing method.…”
Section: Properties Of Polypyrrolementioning
confidence: 99%
“…[ 140 ] The fabrication processes of V 2 O 5 and MnO 2 were a little complex and have been explained elsewhere. [ 141 ] In this work, they used different percentages of V 2 O 5 and MnO 2 with PPY to make different sensors and found that the PPY/4%V 2 O 5 /5%MnO 2 composite provided the best results. They reported a measurement range of 5–60 ppm with an LoD of 5 ppm where the response is 45.67% at 20 ppm NH 3 .…”
Section: Ammonia Gas Sensorsmentioning
confidence: 99%
“…Among the numerous conducting polymers, polypyrrole (PPy) is a kind of p-type conjugated polymer that stands out for its remarkable attributes, including excellent air stability, high electrical conductivity, environmental resilience, and reversible redox properties. , In recent years, composite materials based on PPy have received a great deal of attention. They have been shown to enhance and improve the properties of single inorganic oxides in the research fields of environment and electrochemistry field. Specifically, PPy has also shown promising potential in the field of electrochromism. First, PPy itself is a kind of anodic EC material.…”
Section: Introductionmentioning
confidence: 99%